The Philippine College of Commerce an institutional case study - Roque, Adelaida Lopez
The purpose of the study is to make an institutional case study of the Phlippine College of Commerce by analyzing its objectives, curriculum, physical plant, instructional services and administrative staff, and student characteristics. It aims to determine the relation of the variables to the instructional goals and the degree to which these are achieved.